FDCCII -Based Third-Order Quadrature Sinusoidal Oscillator - Wareechol, Eakluck; Knobnob, Boonying; Kumngern, Montree (My University, 2018)
This paper presents a new mixed-mode third-order quadrature sinusoidal oscillator employing one fully differential second-generation current conveyor (FDCCII), three capacitors and three resistors. The circuit provides two quadrature voltage outputs and two quadrature current outputs into single topology. The condition and frequency of oscillations can be orthogonally controlled. FDCCII-based 0.35±m CMOS process is used to implement and simulate the proposed oscillator.
Keywords: analog circuit; fully differential second-generation current conveyor; mixed-mode circuit; quadrature oscillator